Measures of Fine Motor Skills in People with Tremor Disorders: Appraisal and Interpretation - Norman, Kathleen E.; Héroux, Martin E. (Frontiers in Neurology, 2013)
People with Parkinson’s disease, essential tremor, or other movement disorders involving tremor have changes in fine motor skills that are among the hallmarks of these diseases. Numerous measurement tools have been created and other methods devised to measure such changes in fine motor skills. Measurement tools may focus on specific features – e.g., motor skills or dexterity, slowness in movement execution associated with parkinsonian bradykinesia, or magnitude of tremor. Less obviously, some tools may be better suited than others for specific goals such as detecting subtle dysfunction early in disease, revealing aspects of brain function affected by disease, or tracking changes expected from treatment or disease progression. The purpose of this review is to describe and appraise selected measurement tools of fine motor skills appropriate for people with tremor disorders. In this context, we consider the tools’ content – i.e., what movement features they focus on. In addition, we consider how measurement tools of fine motor skills relate to measures of a person’s disease state or a person’s function. These considerations affect how one should select and interpret the results of these tools in laboratory and clinical contexts.